Um olhar atrás da escrita: o pensamento de Benedito Nunes sobre a Amazônia - GUIMARÃES, Maria Stella Faciola Pessôa (Universidade Federal do Pará, 2012)
The works about Brazilian intellectuals with activities in Amazon are small numbered and usually have gap, mainly when they are analysed out of social context, which makes it harder to know the ideas of those thinkers. In this sense, this dissertation chooses an analysis methodology of Benedito Nunes' thinking based on his texts concerning the Amazon region and relating them with its respective creation contexts. Benedito Nunes was born and always lived in Belém. He has an expressive intellectual production. He won admiration, in Brazil and abroad, for his engagement in the field of philosophy and literary criticism. He wrote seminal papers about Heidegger, Nietzsche, Guimarães Rosa and Clarice Lispector. But the thinker from Pará also wrote essays, granted interviews, wrote forewords, took part in debates and delivered lectures on reflections on history, society and culture from the Amazon, Pará and Belém. In this sense, therefore, he reflects about his own region, and this aspect allows relate him to the study field of Brazilian social thinking. This document analyzes 11 texts by the author in question, duly contextualized, aiming to present a new possibility of reading the works of professor Benedito: as Amazon interpreter that uses, in order to understand the region, the heritage of universal thought that he learned during his accomplished studies. Thus, this dissertation champions the inclusion, as research object of social sciences, of this less revealed part of Benedito's interdisciplinary collection, built during singular intellectual trajectory.